Simulation of process of slider formation on rolling surface of wagon wheel under laboratory conditions - A. V. Obryvalin; D. V. Muraviev; K. V. Averkov; A. A. Rauba (Омский научный вестник)
The article presents the design of a device that makes it possible to investigate in the laboratory conditions the process of formation of a slider on the rolling surface of the wheel. A technique for studying the formation of thermomechanical damages on the rolling surface of a wheel of a freight car is proposed. The results of an experimental study of the motion of a wheel along a rail with the use of physical modeling are presented. An estimation of the change in the properties of the metal of the wheel in the region of thermomechanical damage with the use of metallographic analysis are performed. Conclusions and suggestions are made.